The so-called «punitive damages» in the amendment of Act No 24,240 - Moisá, Benjamín (2008)
In the present article, the author is in favor of the civil fine for unscrupulous acts, this responds to the; therefore, the amount of the sanction must have be destined to the State coffers to avoid the enrichment without cause of the victim. The damage caused by unscrupulous or antisocial behavoir must be that one that by its gravity, social importance or institutional repercussion demands an exemplary sanction, having to be regulated that sanction by the Civil Code. It is for this reason that Sebastián Picasso considers the reform of Law No. 24,240 to be deficient, because it regulates this type of sanction in the personal status of consumers.